Kesehatan Mental Remaja Usia SMA Selama Pandemi Covid 19 (Studi Komparatif Pondok Pesantren Dan Sekolah Umum) - Putri Nurina; Nur Hermatasiyah (Program Studi Bimbingan dan Konseling FKIP Universitas Islam Jember, 2022)
This study aims to compare mental health conditions between students who attend islamic boarding schools and those in public schools that are assessed during the Covid 19 pandemic. It is hoped that using a literature study approach and qualitative methods through open questionnaire techniques and interviews, it will be possible to present a true picture of the mental health situation in both students today. The results showed that students attending boarding schools were more vulnerable to mental health risks compared to students who attended public schools. The COVID-19 pandemic has caused symptoms of PTSD and depression among adolescents aged 16 to 19. This symptom is more commonly experienced by students who attend islamic boarding schools. In general, most respondents are satisfied with online education, but still most students are not comfortable with this new form of learning. The results provide insight into under-researched subjects, helping to highlight potential intervention points to support community mental health programs in the boarding school student population. Keywords: Mental health; high school teenagers; covid 19